Answer:
use (-12)^4
Step-by-step explanation:
Answer:hello the answer is C. 7$
Step-by-step explanation:
Let us always base on the present age. We denote this by x. Now, the age he had 2 years ago would then be denoted as (x-2). Let's equate this to 20 years old.
x - 2 = 20
x = 20 + 2
x = 22 years old
He should be 22 years old now.
Let's check the other condition. After 1 year, his age should be (x+1). Let's equate this to 23 years old.
x + 1 = 23
x = 23 - 1
x = 22
Thus, this is possible if Reuben is 22 years old as of the present.